2019
DOI: 10.1038/s41598-019-46400-8
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Wood Smoke Extract Promotes Barrier Dysfunction in Alveolar Epithelial Cells through a MAPK Signaling Pathway

Abstract: Wildfire smoke induces acute pulmonary distress and is of particular concern to risk groups such as the sick and elderly. Wood smoke (WS) contains many of the same toxic compounds as those found in cigarette smoke (CS) including polycyclic aromatic hydrocarbons, carbon monoxide, and free radicals. CS is a well-established risk factor for respiratory diseases such as asthma and COPD. Limited studies investigating the biological effects of WS on the airway epithelium have been performed. Using a cell culture-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Similarly, after 40-h exposure to 40 μg/cm 2 of wood smoke extract, THP-1 cells entered S/G2 phase of the cell cycle, indicating decreased proliferation [ 23 ]. Studies have also shown evidence of cytotoxicity from exposure to wood smoke by using lactate dehydrogenase (LDH) release assay [ 57 , 58 , 100 , 106 ] or MTT assay [ 168 ], although the positive results were not present in all studies partly due to different wood type, cell line, and doses and exposure duration.…”
Section: Mechanisms Of Cardiovascular Impacts Of Wildfire Smokementioning
confidence: 99%
“…Similarly, after 40-h exposure to 40 μg/cm 2 of wood smoke extract, THP-1 cells entered S/G2 phase of the cell cycle, indicating decreased proliferation [ 23 ]. Studies have also shown evidence of cytotoxicity from exposure to wood smoke by using lactate dehydrogenase (LDH) release assay [ 57 , 58 , 100 , 106 ] or MTT assay [ 168 ], although the positive results were not present in all studies partly due to different wood type, cell line, and doses and exposure duration.…”
Section: Mechanisms Of Cardiovascular Impacts Of Wildfire Smokementioning
confidence: 99%
“…Wildfire smoke may induce acute pulmonary distress, particularly in high-risk groups such as the sick or elderly [ 142 ]. Wood smoke (WS) contains many of the toxic compounds found in CS, including polycyclic aromatic hydrocarbons, carbon monoxide, and free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to CS is a well-established risk factor for respiratory diseases such as asthma and COPD. WS may facilitate the breakdown of alveolar structure via a p44/42 MAPK-dependent pathway, and chronic WS exposure may exacerbate respiratory diseases [ 142 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multifactorial aspect of solution generation results in a difficulty with standardizing protocols. To overcome this challenge, exhaustive detail regarding solution preparation is advisable and can be employed in conjunction with metrics such as optical density, mass spectroscopy, or chromatography (gas and liquid) [ 135 , 136 , 137 ]. Methods used to generate cigarette smoke extract can be found in Table 3 , while eCVE methods can be found in Table 4 .…”
Section: Leveraging Airway On-chip Technology For Inhalation Assaysmentioning
confidence: 99%